Injectivity Evaluation for Offshore CO2 Sequestration in Marine Sediments. (July 2017) - Dai, Zhenxue; Zhang, Ye; Stauffer, Philip; Xiao, Ting; Zhang, Mingkan; Ampomah, William; Yang, Changbing; Zhou, Youqin; Ding, Mei; Middleton, Richard; Soltanian, Mohamad Reza; Bielicki, Jeffrey M.
Abstract: Global and regional climate change caused by greenhouse gases emissions has stimulated interest in developing various technologies (such as carbon dioxide (CO2 ) geologic sequestration in brine reservoirs) to reduce the concentrations of CO2 in the atmosphere. This study develops a statistical framework to identify gravitational CO2 trapping processes and to quantitatively evaluate both CO2 injectivity (or storage capacity) and leakage potential from marine sediments which exhibit heterogeneous permeability and variable thicknesses. We focus on sets of geostatistically-based heterogeneous models populated with fluid flow parameters from several reservoir sites in the U.S. Gulf of Mexico (GOM). A computationally efficient uncertainty quantification study was conducted with results suggesting that permeability heterogeneity and anisotropy, seawater depth, and sediment thickness can all significantly impact CO2 flow and trapping. Large permeability/porosity heterogeneity can enhance gravitational, capillary, and dissolution trapping, which acts to deter CO2 upward migration and subsequent leakage onto the seafloor. When log permeability variance is 5, self-sealing with heterogeneity-enhanced gravitation trapping can be achieved even when water depth is 1.2 km. This extends the previously identified self-sealing condition that water depth be greater than 2.7 km. Our results have yielded valuable insight into the conditions under which safe storage of CO2 can be achieved in offshore environments. The developed statistical framework is general and can be adapted to study other offshore sites worldwide.